THE APPLICATION OF ROBOTIC PROCESS AUTOMATION IN THE FIELD OF ACCOUNTING: A LITERATURE STUDY - Muhammad Nur; Dhieka Avrilia Lantana; Erwin Indriyanto; Kumba Digdowiseiso; Hafiza Aishah Hashim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Accounting seeks to facilitate the process of financial managers gathering financial records, categorizing financial elements, identifying patterns in financial transactions, and conveying financial circumstances. Originally, accounting was performed manually by individuals, but with advancements in technology, robotic process automation (RPA) emerged as a method for carrying out accounting tasks. This implementation has a beneficial effect on the company, resulting in enhanced performance and efficiency. Nevertheless, it has the capacity to generate employment issues. Hence, a comprehensive investigation is required to explore the utilization of robotic process automation in the domain of accounting. The approach employed is a rigorous systematic literature review utilizing scientific publications. The scientific literature utilized must adhere to the specified criteria. The data analysis employs a descriptive and argumentative methodology. The findings indicate that the presence of RPA does not have a substantial capacity to substitute for human involvement. In reality, RPA merely eliminates human tasks, thereby allowing humans to allocate their time towards enhancing more accurate decision-making processes. Occupations within the accounting sector that can benefit from the implementation of RPA encompass bookkeeper, financial accountant, controller (management accountant), business data analyst, treasurer and risk manager, and financial systems and process manager.